Droplet-based synthesis of homogeneous magnetic iron oxide nanoparticles - Ahrberg, Christian D.; Choi, Ji Wook; Chung, Bong Geun (Beilstein Journal of Nanotechnology, 2018)
Nanoparticles have gained large interest in a number of different fields due to their unique properties. In medical applications, for example, magnetic nanoparticles can be used for targeting, imaging, magnetically induced thermotherapy, or for any combination of the three. However, it is still a challenge to obtain narrowly dispersed, reproducible particles through a typical lab-scale synthesis when researching these materials. Here, we present a droplet capillary reactor that can be used for the synthesis of magnetic iron oxide nanoparticles. Compared to conventional batch synthesis, the particles synthesized in our droplet reactor have a narrower size distribution and a higher reproducibility. Furthermore, we demonstrate how the particle size can be changed from 5.2 ± 0.9 nm to 11.8 ± 1.7 nm by changing the reaction temperature and droplet residence time in the droplet capillary reactor.
Keywords: capillary reactor; droplet synthesis; magnetic nanoparticles; narrow size distribution

(untitled) - Stark, W. J. (Angew. Chem., 2011)

(untitled) - Zhang, H.-w.; Liu, Y.; Sun, S.-h. (Front. Phys. China, 2010)

(untitled) - Iqbal, A.; Iqbal, K.; Li, B.; Gong, D.; Qin, W. (J. Nanosci. Nanotechnol., 2017)

(untitled) - Falkenhagen, D. (Artif. Organs, 1995)

(untitled) - Lim, E.-K.; Kim, T.; Paik, S.; Haam, S.; Huh, Y.-M.; Lee, K. (Chem. Rev., 2015)

(untitled) - Lim, J. H.; Kim, D. E.; Kim, E.-J.; Ahrberg, C. D.; Chung, B. G. (Macromol. Res., 2018)

(untitled) - Polyak, B.; Friedman, G. (Expert Opin. Drug Delivery, 2009)

(untitled) - Bao, Y.; Sherwood, J. A.; Sun, Z. (J. Mater. Chem. C, 2018)

(untitled) - Löthman, P. A.; Janson, T.; Klein, Y.; Blaudszun, A.-R.; Ledwig, M.; Abelmann, L. (Int. J. Magn. Part. Imaging, 2017)

(untitled) - Mahmoudi, K.; Hadjipanayis, C. G. (Front. Chem. (Lausanne, Switz.), 2014)

(untitled) - Larson, T. A.; Bankson, J.; Aaron, J.; Sokolov, K. (Nanotechnology, 2007)

(untitled) - Xia, H.; Tong, R.; Song, Y.; Xiong, F.; Li, J.; Wang, S.; Fu, H.; Wen, J.; Li, D.; Zeng, Y.; Zhao, Z.; Wu, J. (J. Nanopart. Res., 2017)

(untitled) - Wacker, J. B.; Lignos, I.; Parashar, V. K.; Gijs, M. A. M. (Lab Chip, 2012)

(untitled) - Rockenberger, J.; Scher, E. C.; Alivisatos, A. P. (J. Am. Chem. Soc., 1999)

(untitled) - Son, Y.-H.; Jung, Y.; Roh, H.; Lee, J.-K. (Nano Convergence, 2017)

(untitled) - Ling, D.; Hyeon, T. (Small, 2013)

(untitled) - Fang, M.; Ström, V.; Olsson, R. T.; Belova, L.; Rao, K. V. (Nanotechnology, 2012)

(untitled) - Kim, D. K.; Zhang, Y.; Voit, W.; Rao, K. V.; Muhammed, M. (J. Magn. Magn. Mater., 2001)

(untitled) - Kumar, K.; Nightingale, A. M.; Krishnadasan, S. H.; Kamaly, N.; Wylenzinska-Arridge, M.; Zeissler, K.; Branford, W. R.; Ware, E.; deMello, A. J.; deMello, J. C. (J. Mater. Chem., 2012)

(untitled) - Gupta, A. K.; Gupta, M. (Biomaterials, 2005)

(untitled) - Manz, A.; Graber, N.; Widmer, H. M. (Sens. Actuators, B, 1990)

(untitled) - Jähnisch, K.; Hessel, V.; Löwe, H.; Baerns, M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Tian, Z.-H.; Shao, M.; Zhao, X.-Y.; Wang, Y.-J.; Wang, K.; Xu, J.-H. (Cryst. Growth Des., 2018)

(untitled) - Uson, L.; Arruebo, M.; Sebastian, V.; Santamaria, J. (Chem. Eng. J., 2018)

(untitled) - Song, H.; Chen, D. L.; Ismagilov, R. F. (Angew. Chem., Int. Ed., 2006)

(untitled) - Choi, J. W.; Lee, J. M.; Kim, T. H.; Ha, J. H.; Ahrberg, C. D.; Chung, B. G. (Nano Convergence, 2018)

(untitled) - Arabinda, B.; Astha, S.; Vandana, S.; Bhanu, P.; Ashok Kumar, G. (Mater. Res. Express, 2018)

(untitled) - Kim, D.-Y.; Jin, S. H.; Jeong, S.-G.; Lee, B.; Kang, K.-K.; Lee, C.-S. (Sci. Rep., 2018)

(untitled) - González-Estefan, J. H.; Gonidec, M.; Daro, N.; Marchivie, M.; Chastanet, G. (Chem. Commun., 2018)

(untitled) - Nightingale, A. M.; Phillips, T. W.; Bannock, J. H.; de Mello, J. C. (Nat. Commun., 2014)

(untitled) - Phillips, T. W.; Lignos, I. G.; Maceiczyk, R. M.; deMello, A. J.; deMello, J. C. (Lab Chip, 2014)

(untitled) - Asuha, S.; Suyala, B.; Siqintana, X.; Zhao, S. (J. Alloys Compd., 2011)

(untitled) - Bhattacharjee, S. (J. Controlled Release, 2016)

(untitled) - Sackmann, E. K.; Fulton, A. L.; Beebe, D. J. (Nature, 2014)

(untitled) - LaMer, V. K.; Dinegar, R. H. (J. Am. Chem. Soc., 1950)

(untitled) - Reiss, H. (J. Chem. Phys., 1951)

(untitled) - Polte, J. (CrystEngComm, 2015)